Rugosidade e porosidade do tecido urbano como critérios de análise qualitativa da ventilação natural em cidades litorâneas - Costa Filho, Amando Candeira (2017)
There is a close interaction between urban planning, city morphology and climate. In order to create adequate environments for human needs, the design of cities must incorporate strategies adapted to the climate at its various scales. Respect for local and global climatic conditions can increase the health of city dwellers by promoting environmental comfort and social life (ZHAO, 2011). Among the bioclimatic attributes related to the urban form, the roughness and the porosity of the urban fabric, have significant interference in the behavior of the natural ventilation. The objective of this thesis is to verify and improve qualitative methods of analysis of the behavior of natural ventilation in coastal cities of hot and humid climate, from the bioclimatizing attributes of height rugosity and distance porosity of the urban fabric. The methods adopted in this research followed experimental and exploratory procedures. In the first moment, qualitative analyzes were carried out related to the bioclimatic attributes of the urban form and its influence on natural ventilation. Each addressed attribute generated a score that was organized into survey cards and the results were spatially exposed on roughness and porosity maps. The three areas of the northern coast of the city of Fortaleza were evaluated and quantitative analyzes of computational simulations were carried out to compare the results obtained in the roughness and porosity maps developed in the qualitative analysis. After the analysis of the results, it was evident that the evaluation of the height, roughness and the porosity of the distance, proved to be valid as a qualitative criterion of the natural ventilation. The different soil occupation situations that were studied had repercussions on the results and the formal attributes were efficient for the analysis of the behavior of the winds. There are recommendations for the improvement of the method: its application in other urban and climatic situations, the insertion of other environmental variables in the analyzes such as the geometry of the sun and other possible bioclimatizing attributes related to natural ventilation.